PENERAPAN LEAN MANUFACTURING Untuk MENGURANGI WASTE Pada PROSES PRODUKSI POMPA INDUSTRI PT.DC - RYAN RINTAKA (2020)
PT.DC is one of the companies engaged in the production of industrial pumps. Good performance of a company is the key for a company to continue to develop towards a better. But there are internal factors in the company such as waste in the form of unnecessary transportation, waiting, unnecessary movements, excessive production, excessive or inappropriate processes, waste of storage and defects in the product. Based on observations made by researchers in this study, this is caused by the many activities that have no added value. This study aims to identify the presence of waste, reduce waste and create recommendations for improvement. Using a lean manufacturing approach, this research begins by making a state map of Big Picture Mapping (BPM) and weighting in the current wastage. The weighting is then analyzed using VALSAT to identify the waste, and also to analyze waste and to make recommendations for improvement with using fishbone and FMEA diagrams. The results showed that the 3 biggest wastes occurred in transportation with an average score of 2.8, waiting with an average score of 2.2 and motion with an average score of 2.2. Proposed improvements can save time necessary but non value added activity and non value added activity from 10868.8 seconds to 8281.2 seconds. Keywords: waste, lean manufacturing, big picture mapping, VALSAT